FISCAL DEFICIT AND THE GROWTH OF DOMESTIC OUTPUT IN NIGERIA - ADAMA, Joseph Ibrahim; OHWOFASA, Bright Onoriode; AYODELE, Victor Ahmed (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
The study focuses on the relationship between fiscal deficit and domestic output (using agricultural output as a proxy) in Nigeria. In other to have a robust model, other parameters of fiscal operations were included as explanatory variables namely, government revenue, government expenditure and government total debt stock. The study argued that even though there are no shortages of theoretical justifications on the impact of fiscal deficit on the national domestic output, empirical probe of the issue is scarcely pursued most especially for the agricultural sector. The model was estimated using the Engle-Granger testing approach to cointegration for the long-run analysis while a restricted error correction model was relied upon to explore the contemporaneous dynamics. The data obtained from Central Bank of Nigeria Statistical Bulletins covered the period 1986-2018. The study found that agricultural output has a long-run relationship with fiscal policy variables. In the long run, the study finds that government revenue and expenditure exert significant positive impact on agriculture output contrarily to the negative impact exhibited by government fiscal deficit and total debt stock. However, in the short run, agriculture output responded negatively to changes in fiscal deficit by 0.03%, government expenditure 0.03% and government total debt stock 0.09% contrarily to its 0.16% response to changes in government revenue. The paper recommended that government may consider reduction in deficit spending so as to minimize the country’s current level of borrowings. Also, government may consider broadening its revenue bases by intensifying its taxation policy. Finally, no effort should be spared by the government in blocking all looped holes in the country’s expenditure operations such as rent seeking and inflation of contracts.